2018
DOI: 10.3389/fneur.2018.00702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthetic Management on Safety and Outcomes Following Mechanical Thrombectomy for Ischemic Stroke in SWIFT PRIME Cohort

Abstract: Background and purpose: The optimal anesthetic management of acute ischemic stroke patients during mechanical thrombectomy (MT) remains controversial. In this post-hoc analysis, we investigated the impact of anesthesia type on clinical outcomes in patients included in SWIFT PRIME trial.Methods: Ninety-seven patients treated with MT were included. Patients treated in centers with general anesthesia (GA) policy (n = 32) were compared with those treated in centers with conscious sedation (CS) policy (n = 65). Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
4
15
1
Order By: Relevance
“…As expected, and in good agreement with several previous reports, mechanical ventilation was also significantly associated with the risk of pneumonia in our cohort in both treatment groups [23,24]. Against the background of this increased risk, there is an ongoing discussion as to whether ET should be performed under conscious sedation or general anesthesia [24].…”
Section: Discussionsupporting
confidence: 93%
“…As expected, and in good agreement with several previous reports, mechanical ventilation was also significantly associated with the risk of pneumonia in our cohort in both treatment groups [23,24]. Against the background of this increased risk, there is an ongoing discussion as to whether ET should be performed under conscious sedation or general anesthesia [24].…”
Section: Discussionsupporting
confidence: 93%
“…However, functional outcomes and mortality rate at discharge and 3 months after stroke were comparable between the two groups. The reason may be due to the fewer DBP fluctuations in our study (45). A meta-analysis also suggested that close monitoring and strictly controlling hemodynamics seem more important regardless of the choice of agents and anesthetic technique (21).…”
Section: Discussionmentioning
confidence: 78%
“…Since all patients in both groups were under general anesthesia during the intervention and we investigated the recanalization itself, we did not analyze anesthesiologic medication or blood pressure during the intervention. In literature, there is evidence for anesthesiologic management influencing outcome, but not recanalization results [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%